Mate vocal recognition in the Scopoli’s shearwater Calonectris diomedea: do females and males share the same acoustic code? - Curé, Charlotte; Mathevon, Nicolas; Aubin, Thierry (Behavioural processes, 2016)
•Vocal mate identification is investigated in a seabird species having a sexual vocal dimorphism.•Playback experiments with natural and modified bird calls are used to compare the reliability of mate vocal recognition in females and males Scopoli’s sheawaters.•Disruption of the call temporal structure, the spectral cues or the envelope structure impaired the mate recognition of both females and males.•We conclude that the coding-decoding process of vocal individual identity is shared by both sexes in this species. Vocal recognition is an important process allowing partners’ reunion in most seabirds. Although the acoustic basis of this recognition has been explored in several species, only a few studies have experimentally tested the acoustic coding-decoding strategy used for mate identification. Here, we investigated mate recognition in the Scopoli’s shearwater (Calonectris diomedea) by conducting playbacks of calls with modified acoustic features. We showed that females and males in a seabird species with a moderate vocal dimorphism are likely to share the same coding-decoding rule for vocal mate identification. Specifically, a disruption of call temporal structure prevented mate recognition in both sexes, in line with the parameters previously identified as supporting an individual signature. Modifications of spectral cues and envelope structure also impaired recognition, but at a lesser extent: almost half of the tested males and females were still able to recognise their partner. It is likely that this equal ability of female and male Scopoli’s shearwaters to vocally recognise their partner could be found in other seabirds.